Information Systems for New Students Assesment at Setia Bhakti Junior High School Using the Simple Additive Weighting (SAW) Method - Felisia Fransiska; Yakub Yakub (Tech-E, 2018)
Technology has a big role in today's life, especially helping the business process activities within a company or organization, making the business process easier. For this reason the creation of a new student admission system and entrance examination in a high school, which affects the speed and accuracy of the final grades in the process. The method used is the Simple Additive Weighting (SAW) method, which has more precise and accurate advantages compared to other decision-making models, because its ability to conduct an assessment is based on the value of criteria and weighted preferences that have been determined. The design and analysis of new student admissions and entrance examination exams can help and overcome existing problems. New student admission and admission test programs have the advantage of being a computerized student registration, conducting computer-based entrance examination exams and can process data through the system thereby reducing the risk of errors in making reports.